Application of laser energy deposition to improve performance for high speed intakes - A. Russell; M. Myokan; H. Bottini; A. Sasoh; H. Zare-Behtash; K. Kontis (Propulsion and Power Research, 2020)
Research interest has been growing in recent years in supersonic transport, particularly supersonic propulsion systems. A key component of a commonly studied propulsion system, ramjets, is the air intake. For supersonic propulsion systems a major factor in the overall efficiency is the intake pressure recovery. This refers to the ratio of the average total pressure after the intake to that of the freestream. One phenomenon that can have a large effect on this performance index is flow separation at the inlet. The aim of this work is to examine how pulsed laser energy deposition can be used to improve pressure recovery performance by reducing flow separation at the inlet. This research examines the effects of pulsed laser energy deposition upstream of an intake with an axisymmetric centrebody in a Mach 1.92 indraft wind tunnel. Laser frequency was varied between 1 and 60 kHz with an energy per pulse of 5.6 mJ. Schlieren photography was used to examine the fundamental fluid dynamics while total and static pressure downstream of the intake diffuser were measured to examine the resulting effect on the performance. Schlieren imaging shows that the interaction between the laser generated thermal bubble and the leading edge shock produced by the centrebody results in a significant reduction in separation along the intake cone. Analysis of the schlieren results and the pressure results in tandem illustrate that the average separation location along the length of the centrebody directly correlates to the pressure recovery observed in the intake. At the optimal laser frequency, found for this Mach number to be 10 kHz, the pressure recovery is found to increase by up to 4.7%. When the laser power added to the system is considered, this results in an overall increase in propulsive power of 2.47%. Keywords: Laser energy deposition, Supersonic, Flow dynamics, Intakes, Flow separation